2023
DOI: 10.1002/hbm.26440
|View full text |Cite
|
Sign up to set email alerts
|

Improved dynamic distortion correction for fMRI using single‐echo EPI and a readout‐reversed first image (REFILL)

Simon Daniel Robinson,
Beata Bachrata,
Korbinian Eckstein
et al.

Abstract: The boundaries between tissues with different magnetic susceptibilities generate inhomogeneities in the main magnetic field which change over time due to motion, respiration and system instabilities. The dynamically changing field can be measured from the phase of the fMRI data and corrected. However, methods for doing so need multi‐echo data, time‐consuming reference scans and/or involve error‐prone processing steps, such as phase unwrapping, which are difficult to implement robustly on the MRI host. The impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Some of those methods require modification to the sequence which may not be desirable, such as jittering the TE, 45 and it has been shown that even for an approach which uses unmodified, single-echo EPI, 46 careful consideration of eddy currents and appropriate corrections are necessary. 47 Our NN approach has similar accuracy to those methods but is more flexible, in that it is expected to be applicable to fast imaging with non-Cartesian readouts (such as spiral and wave). It is also capable of predicting the change of the B 0 with high temporal resolution without measuring extra data during the subsequent sequences in the particular volunteer's MRI acquisitions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some of those methods require modification to the sequence which may not be desirable, such as jittering the TE, 45 and it has been shown that even for an approach which uses unmodified, single-echo EPI, 46 careful consideration of eddy currents and appropriate corrections are necessary. 47 Our NN approach has similar accuracy to those methods but is more flexible, in that it is expected to be applicable to fast imaging with non-Cartesian readouts (such as spiral and wave). It is also capable of predicting the change of the B 0 with high temporal resolution without measuring extra data during the subsequent sequences in the particular volunteer's MRI acquisitions.…”
Section: Discussionmentioning
confidence: 94%
“…In some specific cases (e.g., fMRI), the B 0 maps can be calculated from the phase of single‐echo EPI sequences. Some of those methods require modification to the sequence which may not be desirable, such as jittering the TE, 45 and it has been shown that even for an approach which uses unmodified, single‐echo EPI, 46 careful consideration of eddy currents and appropriate corrections are necessary 47 . Our NN approach has similar accuracy to those methods but is more flexible, in that it is expected to be applicable to fast imaging with non‐Cartesian readouts (such as spiral and wave).…”
Section: Discussionmentioning
confidence: 99%
“…However, acquiring an even number of echoes with rEPI (e.g., two‐echo rEPI) are prone to residual phase errors between odd and even EPI readout lines, as each image is acquired with the same readout gradient polarity. Recent work based on readout‐reversed first echo 13 demonstrated the capability to correct for EPI odd‐even phase errors for fMRI time series, which can be potentially integrated with rEPI to enable robust B0$$ \Delta {B}_0 $$ estimation with an even number of echoes. Note that conventional me‐EPI with under‐sampling can be considered as a special case of rEPI with a large rewinder blip that traverses from − k y_max to k y_max in a single step.…”
Section: Discussionmentioning
confidence: 99%
“…One type of navigator‐free method uses the conventional EPI readout and acquires one EPI image after each excitation. A dynamic B0$$ \Delta {B}_0 $$ map is calculated from the phase of each image volume by subtracting a phase offset term (due to non‐ B 0 related contribution, e.g., B 1 field inhomogeneity) from the image phase and then dividing the residual phase by the TE 9–13 . These methods typically require acquisition of a reference B0$$ \Delta {B}_0 $$ map using conventional multi‐echo gradient echo sequence and use phase extrapolation to obtain reliable phase offset estimation when subject motion is large 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation